ANALYSIS OF MORAL VALUES IN THE ENOLA HOLMES MOVIE - Natalia Sri Kurniati; Eusabinus Bunau; Yanti Sri Rezeki (Sirok Bastra, 2022)
The purpose of this research was to examine the kinds of moral values and describe how they are presented in the Enola Holmes movie directed by Harry Bradbeer. The research design was a descriptive qualitative study and the Enola Holmes movie script was the primary data source. The SPEAKING Model (setting, participants, ends, act sequence, key, instrumentalities, norms, genre) by Dell Hymes is used as the framework to assess the conversation in the movie. The results showed that the movie contained some moral values defined by Haidt such as care, fairness or proportionality, liberty, authority or respect, and loyalty or in group, also moral values defined by Barrow, such as fairness, respect for persons, freedom, and well-being. The most dominant  moral values in this movie were liberty or freedom. The moral values are stated mostly by the characters in the movie directly, while some are stated indirectly. The moral values described in this research have important implications for teachers and other researchers, which encourage the use of various tools in analyzing discourse in literary works and able to apply the moral values in daily life.Keywords: moral value, literature, SPEAKING model, descriptive.